Receptors for the recognition and extraction of lithium - Zhang, Jianfeng; Wenzel, Marco; Yang, Liangrong; Luckay, Robert C.; Weigand, Jan J. (Frontiers in Chemical Engineering, 2023)
Advances in lithium recognition receptors are summarized, focusing on their use as active reagents in circular processes such as liquid-liquid extraction. The latter is an established industrial process that is advantageous due to its large processing capacity and high selectivity. Particularly with regard to the increasing demand for effective separation processes for the recovery of valuable substances from spent lithium-ion batters (LIBs) or the exploration of brines, high-performance systems are required. In this context, the availability of powerful and highly selective receptors are particularly crucial. This mini review summarizes the developments of active receptors for lithium ion extraction and covers advances of receptors for both lithium ions and lithium salts. Various receptor types are discussed, ranging from heteroditopic macrocyclic systems to simple β-diketones. In particular, the latter achieve remarkable high lithium extraction yields in the presence of phosphine oxides such as trioctylphosphine oxide (TOPO). Structural studies employing 4-phosphoryl pyrazolones exhibit diverse coordination modes of lithium and represent clear evidence for the synergistic role of the co-ligand on a molecular level.